The Effect of Nativity, Duration of Residence, and Age at Arrival on Obesity: Evidence from an Australian Longitudinal Study - Santosh Jatrana; Ken Richardson; Samba Siva Rao Pasupuleti (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2018)
The motivation for this paper arises from the lack of longitudinal studies which investigate changes in obesity patterns of immigrants and the effect of age at arrival on these patterns and changes. Additionally, few studies examined empirically the pathways by which changes in obesity occur overtime. We investigated differences in the levels of obesity among foreign-born people from English Speaking and non-English Speaking countries relative to native-born Australians, and how those differences changed with duration of residence and age at arrival using a large representative longitudinal dataset. We also explored whether the association between nativity, duration of residence (DoR) and obesity is mediated by English language proficiency, socioeconomic factors and health behaviour factors. We found that the odds of being obese were significantly smaller among foreign-born people, both from English speaking countries and non-English speaking countries compared with native-born people. Relative to the native-born, immigrants from non-English speaking countries lost their measurable obesity advantage with respect to the native-born after 20 years of residence in Australia, whereas immigrants from English speaking countries did not. We did not find a substantial modification in these associations by age at arrival for either immigrants from non-English speaking or English speaking countries. We found some evidence of a mediating role of English language proficiency on obesity for foreign-born people from non-English speaking countries. Given increasing proportions of foreign-born people in Australia, particularly from non-English speaking countries, our results underscore the role of English language proficiency in designing healthy weight interventions.
Keywords: 300; Nativity; longitudinal studies; obesity; Australia